Assessing the Socio-economic Impact and Post-pandemic Recovery of Bhaktapur's Tourism Sector - Bohara, Pradeep Kumar; Khanal, Tantrika Raj (DEPAN, 2025)
Background: The COVID-19 pandemic caused significant disruptions to the global tourism industry, including business, economic instability, and a substantial loss of jobs. One of the hardest-hit industries, tourism, was almost entirely shut down by travel restrictions and health controls. Numerous companies that depended on tourism suffered, and Bhaktapur, a city in Nepal famous for its UNESCO World Heritage sites, saw severe economic effects.Methodology: This study assesses the socioeconomic effects of the COVID-19 pandemic on Bhaktapur's tourism industry using primary and secondary data sources. A comparison of pre-pandemic and post-pandemic tourism patterns was conducted using surveys and interviews with residents, entrepreneurs, and staff members of the tourism sector. The collected data was examined using statistical tools such as correlation analysis, trend analysis, and percentage changes.Results: The findings show a dramatic decline in tourism-related income and employment, with visitor arrivals in 2020–21 falling by 98.5% from 2019–20. The socioeconomic effects, which were especially apparent among small businesses, street vendors, and local guides, worsened the poverty and economic instability in the area.Conclusion: The findings indicate the need for recovery plans that are urgently focused, such as investments in digital marketing, infrastructure upgrades, and public-private partnerships, in order to boost Bhaktapur's tourism industry. Additionally, government initiatives should focus on improving resilience in order to safeguard the travel and tourism industry from future global crises.